Reactive spark plasma sintering of Cs-exchanged chabazite: characterisation and durability assessment for Fukushima Daiichi NPP clean-up. Issue 9 (3rd October 2019) - Harnett, Liam. C.; Gardner, Laura. J.; Sun, Shi-Kuan; Mann, Colleen; Hyatt, Neil. C.
ABSTRACT: Ion-specific media (ISM) have played an integral role in the clean-up and remediation efforts at the Fukushima Dai-ichi disaster site, through the processing of contaminated wastewaters. The use of these materials generates a secondary nuclear waste stream, presenting its own series of engineering problems arising from stringent handling and long-term storage requirements. A reactive spark plasma sintering (SPS) method was investigated for conditioning of the spent cesium exchanged zeolite, chabazite. A natural form of the zeolite was used as an analogue to the engineered ISM used at the Fukushima NPP site. Simulant wasteforms were sintered using different temperature and pressure parameters followed by analysis of phase assemblage, density, and durability (using the product consistency test (PCT)). The results indicated that zeolite structure had collapsed completely, with the exchanged cesium partitioned primarily into a durable feldspar to assure stability of the sintered material for passively safe storage or geological disposal.